STEM Education Planning Based on Contextual Issues Sustainable Development Goals (SDGs) - Oktian Fajar Nugroho; Silvia Ratna Juwita; Nurul Febrianti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
In the pursuit of enhancing students' and instructors' engagement in STEM education, this study integrates existing STEM courses into the Indonesian curriculum to tackle real-world issues. The primary objective is to address significant global problems aligned with the Sustainable Development Goals (SDGs) at the junior high school level. To achieve this, the current curriculum requirements for all three STEM subjects are interwoven. Document analysis, involving standard papers from three distinct STEM fields, curriculum maps for schools, and materials related to 'Continuing Development Education,' serves as the primary data collection method. This article outlines the planning process for after-school STEM education programs. It draws inspiration from the SDGs, presenting four design challenges that incorporate standards from three STEM domains. These challenges encompass fresh, interconnected concepts and skills. This description provides educators with a framework for creating lessons and STEM educational activities that fuse curricular requirements with existing STEM disciplines, catering to various levels and student settings.